Perbedaan Toksisitas Larutan Buah Pare (Momordica charantia Linnaeus) dan Buah Belimbing Wuluh (Averrhoa bilimbi Linnaeus) Sebagai Biolarvasida Culex Sp - Alifatun Khunafa'; Ngadino Ngadino; Hadi Suryono; Aries Prasetyo (FORIKES, 2020)
One strategy to overcome the case of filariasis is by turning off the vector, namely Culex sp. Mosquitoes, and usually using chemicals as larvicides, in the long run, can cause resistance to larvae and environmental pollution. Bitter melon (Momordica charantia Linnaeus) and cucumber tree fruit (Averrhoa bilimbi Linnaeus) can cause death in larvae because they contain chemical compounds alkaloids, flavonoids, saponins, tannins, and are safe for animals and the environment. This study aims to determine the differences in the toxicity of Bitter melon fruit (Momordica charantia Linnaeus) and cucumber tree fruti (Averrhoa bilimbi Linnaeus) as Culex sp bio-larvacides. The research method was experimental, with the research design used is the post-test only control group design. Samples were Culex sp. third instar mosquito larvae. The study used 4 replications and 7 treatments with 25 larvae of each treatment. The concentration of bitter melon fruit (Momordica charantia Linnaeus) and cucumber tree fruit (Averrhoa bilimbi Linnaeus) were 0% (control); 11%; 22%; 44%. Data analysis was performed analytically using a probit test and a different test (Two Way Anova). The results showed a solution of bitter melon fruit (Momordica charantia Linnaeus) and cucumber tree fruit (Averrhoa bilimbi Linnaeus) had the potential as a bio-larvacide and had a mortality rate at 0% concentration (control), in bitter melon fruit concentrations of 11%; 22%; 44% of 73%, 89%, 100%. Whereas in cucumber tree fruit concentration 11%; 22%; 44; by 95%, 99%, 100%. The different test showed that there was a significant difference between control, bitter melon (Momordica charantia Linnaeus) and cucumber tree fruit (Averrhoa bilimbi Linnaeus) solution to Culex sp larvae mortality (α